Designing Hola Grafika’s Brand Communication Strategy to Increase Interaction with Consumers on Instagram - Tantra, Geralda Carnelian (VCD, 2025)
This research explores the correlation between design and visual communication in the context of increasing brand emergence in the digital era. The rapid growth of new brands has intensified competition for audience attention, creating a challenge for brands to remain relevant and memorable. To address this, strategic brand communication is essential—particularly on platforms like Instagram, where interaction and visual content play a key role in audience engagement. This study focuses on Hola Grafika, a design-focused brand facing challenges in establishing strong engagement with its target audience aged 20–25 years old. The research aims to identify an effective brand communication method, define appropriate content strategies, and determine suitable visual approaches to enhance interaction. Data collection involved interviews with expert users in branding, digital marketing, and design, as well as with extreme users, followed by micro market-tests with Instagram users who use the platform to seek design inspiration and educational content.